KEESAAN TUHAN DAN PETA WILAYAH KOGNITIF TEOLOGI HINDU: KAJIAN PUSTAKA TENTANG PLURALITAS KONSEP TEOLOGI DALAM HINDU - I Ketut Donder (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
All religions worship to one God yet they have different ways to understand and pray. They teach transcendental concept that is not easy to understand. Therefore, it is required a knowledgeable spiritual teacher to understand the religion properly. Different understandings on transcendental concept are caused by different religious level that someone has. The Hindu sages have solved this problem by providing two areas of cognitive theology, namely Nirguna Brhman and Satguna Brahman and each is divided further into their subtheologies. The various Hindu theologies aim to bring human beings whose different religious level having same understanding on God. It can avoid misconception on Hindu teaching.